Performance of two-dimensional Doppler echocardiography for the assessment of infarct size and left ventricular function in rats - Nozawa, E. [UNIFESP] (2006)
Although echocardiography has been used in rats, few studies have determined its efficacy for estimating myocardial infarct size. Our objective was to estimate the myocardial infarct size, and to evaluate anatomic and functional variables of the left ventricle. Myocardial infarction was produced in 43 female Wistar rats by ligature of the left coronary artery. Echocardiography was performed 5 weeks later to measure left ventricular diameter and transverse area (mean of 3 transverse planes), infarct size (percentage of the arc with infarct on 3 transverse planes), systolic function by the change in fractional area, and diastolic function by mitral inflow parameters. The histologic measurement of myocardial infarction size was similar to the echocardiographic method. Myocardial infarct size ranged from 4.8 to 66.6% when determined by histology and from 5 to 69.8% when determined by echocardiography, with good correlation (r = 0.88; P < 0.05; Pearson correlation coefficient). Left ventricular diameter and mean diastolic transverse area correlated with myocardial infarct size by histology (r = 0.57 and r = 0.78; P < 0.0005). The fractional area change ranged from 28.5 ± 5.6 (large-size myocardial infarction) to 53.1 ± 1.5% (control) and correlated with myocardial infarct size by echocardiography (r = -0.87; P < 0.00001) and histology (r = -0.78; P < 00001). The E/A wave ratio of mitral inflow velocity for animals with large-size myocardial infarction (5.6 ± 2.7) was significantly higher than for all others (control: 1.9 ± 0.1; small-size myocardial infarction: 1.9 ± 0.4; moderate-size myocardial infarction: 2.8 ± 2.3). There was good agreement between echocardiographic and histologic estimates of myocardial infarct size in rats.